Do the origins of primary teeth affect the bond strength of a self-etching adhesive system to dentin? - Camilla Regina Galvão Bengtson; Antonio Lucindo Bengtson; Nadya Galvão Bengtson; Miriam Lacalle Turbino (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The aim of this in vitro study was to evaluate the tensile bond strength of a self-etching adhesive system to three different dentinal substrates. Primary molar teeth that had been recently exfoliated (RE), with unknown time of exfoliation (UT), and extracted due to prolonged retention (PR) were used for this investigation. Ten primary molar teeth of each group were cut in the middle following the mesio-distal direction, creating a total of twenty specimens per group. The specimens were included in acrylic resin and had a flat dentin surface exposed. The self-etching adhesive system was applied to this surface and a 3-millimeter high cone with diameter of 2 mm in the adhesion area was constructed using composite resin. The specimens were stored in distilled water at 37ºC for 24 hours. Fifteen specimens of each substrate were used for the tensile bond test (n = 15) and 5 had the interface analyzed by scanning electron microscopy (SEM). The data was examined by one-way ANOVA and presented no significant differences between groups (p = 0.5787). The mean values obtained for RE, UT and PR were 18.39 ± 9.70, 19.41 ± 7.80, and 23.30 ± 9.37 MPa, respectively. Any dentinal substrates of primary teeth studied are safe for tensile bond strength tests with adhesive systems.